2006
DOI: 10.1007/s11908-006-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in the pathophysiology of infective endocarditis

Abstract: Endocarditis pathogens colonize valves with pre-existing sterile vegetations or valves with minimal endothelial lesions. Inflamed endothelia produce cytokines, integrins, and tissue factor, which in turn attract fibronectin, monocytes, and platelets. Bacteria attaching to such structures further activate the cascade, becoming embedded and protected from host defenses. Staphylococcus aureus also actively invade the endothelium, causing apoptosis and endothelial damage. Knowledge of this interplay identifies hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 51 publications
2
53
0
4
Order By: Relevance
“…In the same line, a few LPXTGproteins were not detected at all (i.e. Srap and SasC) in S. aureus Newman, although they were detected by LC-MS/MS in recombinant lactococci (35,41). This raises the question of their conditional expression, as observed in the present experiments and by others for isd genes (32,33), or of differential access of trypsin digestion.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the same line, a few LPXTGproteins were not detected at all (i.e. Srap and SasC) in S. aureus Newman, although they were detected by LC-MS/MS in recombinant lactococci (35,41). This raises the question of their conditional expression, as observed in the present experiments and by others for isd genes (32,33), or of differential access of trypsin digestion.…”
Section: Discussionsupporting
confidence: 66%
“…We previously showed that LPXTG-proteins from S. aureus could be heterogeneously expressed in L. lactis and individually detected by LC-MS/MS in the recombinant lactococci (35,41). On this basis we constructed a peptide library specific to each of these LPXTG-proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin-binding protein A and B (FnBPA/FnBPB) and Clumping Factor A (ClfA) are wellcharacterized Microbial Surface Components Recognizing Adhesive Matrix Molecules (MSCRAMMs) that mediate attachment and colonization of S. aureus to the heart endothelium and medical devices (16)(17)(18)(19). The capsular polysaccharide is another important virulence factor expressed by most clinical strains of S. aureus.…”
mentioning
confidence: 99%
“…Kapak sklerozu, vaskülit veya direkt bakteri aktivitesi (Staphylococcus aureus gibi) endotel hasarına yol açmaktadır. 7 Fibronektin, stafilokokal "clumping" faktör A ve B gibi adezyon proteinleri bakterilerin yapışmasında önemli bir role sahiptir. 7,8 Bakteri kolonizasyonu, endotel hasarını ve trombüs oluşmasını/büyüme-sini tetiklemektedir.…”
Section: Fi̇zyopatoloji̇unclassified
“…7 Fibronektin, stafilokokal "clumping" faktör A ve B gibi adezyon proteinleri bakterilerin yapışmasında önemli bir role sahiptir. 7,8 Bakteri kolonizasyonu, endotel hasarını ve trombüs oluşmasını/büyüme-sini tetiklemektedir. Polisakkarit ve protein matriks içeren çok katmanlı bakteri kümeleri (agregatlar) oluşmaktadır.…”
Section: Fi̇zyopatoloji̇unclassified